Investigating eighth-grade students’ conceptual understanding of cartesian coordinates in junior high school mathematics - Sihombing, Karlina Mutiara (CV. Pustaka Literasi Ilmiah, 2025)
Understanding mathematical concepts is a crucial aspect of learning mathematics, as it enables students to solve problems, reason logically, and apply knowledge in various contexts. This study aimed to analyze eighth-grade students’ conceptual understanding of Cartesian coordinate material. The population of this research consisted of junior high school students in a school located in the Karawang district, with a sample of 30 students from class VIII. Data were collected using a mathematical comprehension test consisting of four questions, each designed to assess specific indicators of conceptual understanding, including identifying points, determining direction and distance, and analyzing the relative positions of lines. The results showed that students frequently made errors in several areas: many struggled to accurately identify points on the Cartesian plane, had difficulty determining direction and distance from a given point, and often misinterpreted the positions of lines relative to one another. These findings indicate that students’ conceptual understanding of Cartesian coordinates remains limited, which may hinder their overall mathematical performance. Therefore, it is recommended that teachers implement more targeted instructional strategies, such as visual representations, guided practice, and interactive exercises, to enhance students’ comprehension and strengthen their mathematical reasoning skills. The contribution of this study lies in providing empirical evidence on students’ specific misconceptions related to Cartesian coordinates and offering pedagogical implications that can inform the development of more effective instructional approaches in mathematics classrooms.